SOSIAL MEDIA ADVERTISING PADA SMK HANG NADIM BATAM - Koko Handoko; Wasiman Wasiman; Pastima Simanjuntak (PUAN INDONESIA, 2023)
In the era of technology where development is so fast where everyone on average has a mobile phone, those who have sophisticated mobile phones must have social media. Social media is one of the media that is developing very rapidly in the world. Social media used such as Facebook and Instagram, Facebook is used not only by teenagers but now parents use Facebook more, but more teenagers use Instagram than parents. Because generally now people, especially teenagers, use two social media on top of serving as teaching how to make an advertisement on their respective social media for students of Hang Nadim Batam Vocational School, the goal is that now students can learn to make a business or sell other people's products using a promotion that done using social media respectively. Product marketing or selling other people's products will be more effective through social media that we use whether we are looking for new customers or retaining existing customers.